Redeveloping the world’s largest Social Science library for the 21st century - Sykes, Jean (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
The complete redevelopment of the LSE’s library, built in 1916 as a book warehouse and purchased by LSE in 1978, was first discussed in the early 1990s. By this time it had become clear that the library needed major changes to make it fit for the future. The environmental conditions were poor for the valuable print collections (too hot and too dry) and for the users (stuffy and cramped). The layout was confusing, making it difficult for people to find their way round: a large internal ’light well’ from the first floor upwards caused problems of circulation, inefficiency of space use, and did not actually cast much light into the building at all. And the infrastructure of the building was not suitable for the huge growth in use of computers, with the result that ugly bolt-on wiring had been employed in certain parts of the library to accommodate 150 PCs, with very little flexibility for further expansion.